Q: What is -3p squared plus p squared?

Write your answer...

Submit

Still have questions?

Continue Learning about Algebra

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

p+2 = 2-3p p+3p = 2-2 4p = 0 p = 0

3p2-2p-5 = (3p-5)(p+1) when factored

4p+2 = 3p-7 4p-3p = -7-2 p = -9

It is an expression that can be simplified to: 3p+q

Related questions

3p

answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}

3p+5+p = -23 3p+p = -23-5 4p = -28 p = -7

-5 + 3p - p = -5 + 2p

p2 + 3p = p (p + 3)

p+2 = 2-3p p+3p = 2-2 4p = 0 p = 0

3p plus 7 equals 34, where P is equivalent to number 9.

3p2-2p-5 = (3p-5)(p+1) when factored

6

6

3p+7 = 16+2p 3p-2p = 16-7 p = 9

4p+7q